Experimental Evaluation of the Durability of Concrete Repair Materials - Tae-Kyun Kim; Jong-Sup Park (Applied Sciences, 2021)
Concrete structures crack as they age due to deterioration phenomena such as carbonation, chloride attack, and freeze–thaw. Cracks may also occur due to corrosion of steel reinforcements, which can rapidly degrade the structural integrity. Therefore, this study uses strength and durability tests to examine the materials used to repair cracks in concrete; namely, epoxy, impregnant, and epoxy/impregnant. The results show that epoxy has the greatest strength; epoxy/impregnant is most effective for repairing carbonation damage; impregnant is most effective for repairing chloride damage; epoxy and epoxy/impregnant are most effective for repairing freeze–thaw damage, depending on environmental and physical factors, as well as the crack width. These results can be used to improve the quality of repairs and increase the safe operating life of structures.